Pengaruh Avicel PH 102 Terhadap Karakteristik Fisik dan Laju Disolusi Orally Disintegrating Tablet Piroksikam Dengan Metode Cetak Langsung - Setyawan, Dwi; Widjaja, Bambang; Ningtyas, Zimy Fianti (UI Scholars Hub, 2010)
The influence of Avicel PH 102 as disintegrant on physical characteristic and dissolution rate of piroxicam Orally Disintegrating Tablet prepared by direct compression method was observed in this research. Concentration of Avicel PH 102 used were 5%, 10%, 15% and 0% as a control. Physical characteristics of the powder blend including flow rate and angle of repose showed good attributes. The powder blend was pressed into tablet by hydraulic press with a pressure of 1 ton and diameter of 8 mm. The physical characteristic of piroxicam orally disintegrating tablet including hardness, friability, disintegration time, and dissolution rate were examined. The hardness of all formulas were between 0,99 – 2,78 kP, friability were between 3,45% – 1,25%, disintegration time were between 223,67– 18,33 sec and drug released at 45 minutes were between 32,71%– 88,63%. The results showed that increasing the concentration of Avicel PH 102 would increase the hardness, and dissolution rate and decrease the friability and disintegration time of piroxicam orally disintegrating tablet . From statistical analysis (µ = 0,05), it could be seen that there was significant difference in physical characteristics and dissolution rate of all formulas. Among all formulas, it could be concluded that formula with 10% concentration of Avicel PH 102 was the optimum formula